Where have all the countries of origin gone? A note on the neglect of firm nationality in family business studies. Issue 3 (8th October 2018) - Machek, Ondrej
Abstract : Purpose: The purpose of this paper is to present arguments for the inclusion of greater sampling detail in comparative studies of family business that includes country of origin/ownership. Design/methodology/approach: This paper is a commentary piece from a scholar focused on family business studies. Findings: This commentary paper challenges several past family business studies and argues that mixing small family firms with foreign-owned family firms (subsidiaries of foreign companies) into one research sample of "family firms" can represent a significant source of bias. The authors assume that this bias is likely to be more pronounced in samples of privately-held family firms. Originality/value: While most of the author'sknowledge on family firms is based on analyses of publicly-held firms, current editors of scholarly journals call for more research on privately-held firms since they represent the vast majority of firms worldwide. The development of the knowledge about private family firms crucially depends on the reliability of results. This paper emphasizes the need for research samples of comparable firms and more comments on the sampling process.